2016
DOI: 10.1016/j.poly.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

95Mo NMR study of the effect of structure on complexation of molybdate with alpha and beta hydroxy carboxylic acid ligands

Abstract: 95 MoNMR study of the effect of structure on complexation of molybdate with alpha and beta hydroxy carboxylic acid ligands Abstract The utility of the quadrupolar, spin 5/2 95 Mo nucleus in NMR studies of complexation of molybdate have been demonstrated using model alpha hydroxyl carboxylic acids. The 95 Mo NMR spectra show a down field shift of the resonance upon complexation, presumably due to the smaller 1/∆E paramagnetic shift term for the octahedral molybdate complexes relative to the tetrahedral molybdat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The shift of the resonances of the phenoxy carbons to higher chemical shifts (158 ppm) are attributed to the electrophilic effect of molybdate groups reducing the shielding of the phenoxy carbons. 15 The broadened chemical shifts (152–158 ppm) of the phenoxy carbons illustrate that the molybdate groups entered the phenolic molecular chain.…”
Section: Resultsmentioning
confidence: 99%
“…The shift of the resonances of the phenoxy carbons to higher chemical shifts (158 ppm) are attributed to the electrophilic effect of molybdate groups reducing the shielding of the phenoxy carbons. 15 The broadened chemical shifts (152–158 ppm) of the phenoxy carbons illustrate that the molybdate groups entered the phenolic molecular chain.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that, during complexation, Mo(VI) in molybdate often expands its coordination, usually from 4 (tetrahedral) to 6 (octahedral) [35]. Moreover, several structures have been reported in which strong binding, e.g., by catecholates or hydroxopyridinones, leads to MoO 3 and/or MoO 2 2+ moieties [36][37][38]: every oxygen atom from the original molybdate is "lost" during complexation through the formation of a water molecule that, from a mere stoichiometric point of view, corresponds to the involvement in the formation equilibrium of two protons per "lost" oxygen (of course they can be donated by the ligand itself).…”
Section: Identification Of (Moo 4 ) P (8-hqa) Q H R Species and Coordmentioning
confidence: 99%